Allergic rhinitis caused by plant pollen in adolescents - G. M. Nurtdinova; E. S. Galimova; S. G. Khamidullina; V. K. Muslimova; A. I. Gareeva; D. O. Galimov (Аллергология и Иммунология в Педиатрии)
Background. Allergic rhinitis is caused by grass pollen is a common problem in the world. The symptoms of this disease can varied on the age of the patient.   Aim: to identify the etiology and analyze the clinic of allergic rhinitis in adolescents.   Methods. An allergic examination was carried out in 96 patients with allergic rhinitis signs who were treated at MEGI MC, which included the study of an allergic history and setting of scarification tests, determination of IgE, comparison of clinical manifestations and detection of sensitization to pollen of various plants in adolescents with allergic rhinitis.   Results. The prevailing share of girls was 65.4 %. The etiological factors were tree pollen in 28.6 % of cases (in 27 patients), weeds – 12.4 % (12 people), meadow grasses – 10.6 % (10 people), meadow and weeds – 8.3 % (8 people), a combination of trees, meadow and weeds – 6.4 % (6 people) and trees and meadow grasses – 4.7 % (4 people).   Conclusion. Typical clinical manifestations consist of light and middle rhinitis  – 71 people (94 %), conjunctivitis – 45 people (58.8 %), rhinosinusitis – 22 people (28.6 %), bronchial asthma – 10 people (10.4 %).